Main trends in modern Josephus research - Bilde, Per (Nordisk judaistik/Scandinavian Jewish Studies, 1987)
Josephus was a Jewish historian during the 1st century in the Roman Empire. In the Christian church, Josephus received recognition as a crypto-Christian Nicodemus character, a kind of Jewish church father similar to Philo, or a kind of fifth evangelist. In late antiquity and the Middle Ages of Europe he was respected and esteemed as a great author and historian. For example, a man like Hieronymus would describe him as the Jewish Livius. During this period, admiration of him was nearly uncritical, and the work of scholars consisted primarily in carrying on the tradition by constantly creating new editions and translations. The first slight signs of critical attitude appeared at the end of the Middle Ages, when one gradually began to take note of and comment on Josephus’ deviations from the text of the Old Testament in his rendering of biblical history.